Examining Audit Fee Determinants and Their Impact on Audit Quality - Wahyuni, Wahyuni; Sueny, Lindah Nurul Rila; Wahyu, Aisyah Salma; Fadewa, Nurhalisa Nur (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to identify the determinants of audit fees and their impact on audit quality. It also explores the relationship between audit fees, firm characteristics, market dynamics, and industry regulation. Research Design and Methodology: This research uses a systematic literature review method by collecting and analyzing relevant articles, books, and conference papers from academic databases such as PubMed, Google Scholar, and Web of Science. The keywords used included “audit fees”, “audit quality”, “determinants”, and “regulatory reform”. The selected studies were evaluated based on research design, sample size, data collection methods, and theoretical rigor to ensure their validity and reliability. Findings and Discussion: The results show that firm-specific attributes such as size, complexity, and financial performance are critical determinants of audit fees. Larger and more complex firms tend to face higher audit fees as they require more effort and resources to audit their operations. Industry-specific factors, including regulatory requirements and market dynamics, are essential in determining audit fees. The study also found higher audit fees are generally associated with increased audit effort and professional skepticism. However, fee pressure and client negotiating power may affect auditor independence and reduce audit quality. Implications: This study has significant implications for academic research and professional practice in auditing. A deeper understanding of audit fee determination mechanisms and their impact on audit quality can aid in developing evidence-based policies and practices that enhance financial reporting transparency and investor confidence. In addition, exploring emerging trends, such as the impact of regulatory reforms and technological innovations on audit fee dynamics, emphasizes the importance of ongoing research to keep pace with developments in the audit profession. Multidisciplinary collaborations and comparative studies across jurisdictions offer additional insights that enrich understanding audit cost determinants from multiple perspectives.